Post-Islamism and Intellectual Production: A Bibliometric Analysis of the Evolution of Contemporary Islamic Thought - Brahimi, Mohamed Amine (Religions, 2021)
The advent of the 1990s marked, among other things, the restructuring of the Muslim world in its relation to Islam. This new context has proved to be extremely favorable to the emergence of scholars who define themselves as reformists or modernists. They have dedicated themselves to reform in Islam based on the values of peace, human rights, and secular governance. One can find an example of this approach in the works of renowned intellectuals such as Farid Esack, Mohamed Talbi, or Mohamed Arkoun, to name a few. However, the question of Islamic reform has been debated during the 19th and 20th centuries. This article aims to comprehend the historical evolution of contemporary reformist thinkers in the scientific field. The literature surrounding these intellectuals is based primarily on content analysis. These approaches share a type of reading that focuses on the interaction and codetermination of religious interpretations rather than on the relationships and social dynamics that constitute them. Despite these contributions, it seems vital to question this contemporary thinking differently: what influence does the context of post-Islamism have on the emergence of this intellectual trend? What connections does it have with the social sciences and humanities? How did it evolve historically? In this context, the researchers will analyze co-citations in representative samples to illustrate the theoretical framework in which these intellectuals are located, and its evolution. Using selected cases, this process will help us to both underline the empowerment of contemporary Islamic thought and the formation of a real corpus of works seeking to reform Islam.